AN EFFECTIVE MOOC MODEL TO SUPPORT FREEDOM TO LEARN PROGRAM - Ahmad Chafid Alwi; Siti Irene Astuti Dwiningrum; Suyanto Suyanto; Sunaryo Sunarto; Surono Surono (Universitas Negeri Yogyakarta, 2021)
This study was aimed at exploring an effective and proper MOOC model which is in line with the learning need of Indonesian society, especially in pandemic era. This study was conducted by employing Content Analysis in IndonesiaX and sekolahpintar.com platforms. The data obtained were analysed by identifying the differences and the similarities of each MOOC. The results show that a good MOOC model such as IndonesiaX has a more structured presentation of content, videos with fresh visuals and excellent evaluation. The questions presented also not only measure low order thinking skills, but also present high order thinking skills questions that are not available at SekolahPintar.com. An effective MOOC model must meet the CDT (Component Display Theory) and dimensions of effective online learning, be able to motivate students to learn independently and be able to create student involvement in collaborative discussions. The motivation is more effective if it is continuously aroused by delivering proper strategies, which is in line with the need.